African Studies in Russia : Works of the Institute for African Studies of the Russian Academy of Sciences Yearbook 20142016 (Book collections on Project MUSE., 2017)
"The publication is the latest in the African Studies in Russia series of compilations and contains full articles and annotations of the most important - from the point of view of editors - works of Russian Africanists over a certain period. The authors work at the Institute for African Studies of the Russian Academy of Sciences (RAS). The present issue covers the years 2014 to 2016 and consists of two sections. The first section presents conceptual articles on Africa published in authoritative journals. The second section offers synopses of books by Russian authors on economics, cultural anthropology, social and political development, gender studies, and international relations of African countries. The main objective of the triennial series of compilations is to introduce new findings of Russian Africanists to interested foreign scholars who do not speak Russian."